2015
DOI: 10.12972/ksmer.2015.52.5.511
|View full text |Cite
|
Sign up to set email alerts
|

GIS Based Algorithm for Monitoring of Spilling of Acid Mine Drainage in Mining Area

Abstract: Mine hazards has distributed nationally through the abandoned mine areas, and stream water contamination by acid mine drainage threats resident's health and agricultural industry. To support stream water monitoring for spilling acid mine drainage, new techniques should be required. This study proposed the algorithm for choosing monitoring position, estimating source of acid mine drainage, comparing putative sources with path distance, passing time, and EFH index. The algorithm was applied to field data and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In addition, the results of GIS-based algorithms for calculating the single-flow direction in a DEM were examined by concave- and convex-shaped topography, and software was developed to allow users to apply the algorithms effectively. Yi et al [ 26 ] suggested a technique to propose AMD monitoring points, by identifying where the water systems meet, with consideration of the shape of the stream. Furthermore, a method to evaluate putative AMD sources based on mine location and monitoring points was designed in the study.…”
Section: Water Pollution and Drainage Controlmentioning
confidence: 99%
“…In addition, the results of GIS-based algorithms for calculating the single-flow direction in a DEM were examined by concave- and convex-shaped topography, and software was developed to allow users to apply the algorithms effectively. Yi et al [ 26 ] suggested a technique to propose AMD monitoring points, by identifying where the water systems meet, with consideration of the shape of the stream. Furthermore, a method to evaluate putative AMD sources based on mine location and monitoring points was designed in the study.…”
Section: Water Pollution and Drainage Controlmentioning
confidence: 99%